2021
DOI: 10.1039/d1dt00648g
|View full text |Cite
|
Sign up to set email alerts
|

Dual sensing of methionine and aspartic acid in aqueous medium by a quinoline-based fluorescent probe

Abstract: Quinoline based Schiff base 6-methyl-2-oxo-1,2-dihydro-quinoline-3carboxaldehyde-4(N)-phenylsemicarbazone (6MPS) sensor has been developed for selective sensing of methionine and aspartic acid in aqueous medium through selective detection of copper ion as “on-off-on” type....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Therefore, designing a chemosensor that can selectively detect an amino acid is always difficult [ 77 ]. Chemosensors L1 and L2 containing electron-rich groups and various binding sites make them ideal for the detection of amino acids [ 27 , 29 ]. Hence, the detection ability of L1 and L2 was checked towards all 20 amino acids: Gly, Ala, Glu, Pro, Cys, Ile, Tyr, Arg, Gln, Lys, Thr, Asp, Asn, His, Leu, Met, Phe, Ser, Trp, and Val.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, designing a chemosensor that can selectively detect an amino acid is always difficult [ 77 ]. Chemosensors L1 and L2 containing electron-rich groups and various binding sites make them ideal for the detection of amino acids [ 27 , 29 ]. Hence, the detection ability of L1 and L2 was checked towards all 20 amino acids: Gly, Ala, Glu, Pro, Cys, Ile, Tyr, Arg, Gln, Lys, Thr, Asp, Asn, His, Leu, Met, Phe, Ser, Trp, and Val.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst all nonessential amino acids, Aspartic Acid (Asp) plays several critical roles in various biological and physiological processes [ 24 , 25 , 26 ]. Asp is specifically required for its role in the tricarboxylic acid (TCA) cycle [ 27 , 28 ]. Asp also serves as the main precursor for the synthesis of two amino acids, i.e., Glutamic acid and Glycine [ 24 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical Methods off-on" type of mechanism. 75 Ligand 63 initially exhibited uorescence but the addition of Cu 2+ resulted in the sudden quenching of the uorescence intensity. Upon the addition of aspartic acid/methionine to the complex solution, a notable increase in the uorescence intensity was observed.…”
Section: Minireviewmentioning
confidence: 99%
“…Prabhakaran et al reported the copper( ii ) complex of a quinoline-based Schiff base sensor ( 63 ) for the selective detection of methionine in aqueous medium through an “on–off–on” type of mechanism. 75 Ligand 63 initially exhibited fluorescence but the addition of Cu 2+ resulted in the sudden quenching of the fluorescence intensity. Upon the addition of aspartic acid/methionine to the complex solution, a notable increase in the fluorescence intensity was observed.…”
Section: Chemosensors For the Selective Detection Of Methionine (Met)mentioning
confidence: 99%